Estrategias para el desarrollo de la competencia comunicativa en la fase de la preescritura - Madrigal Abarca, Marta (2012)
The process to the written form concepts, ideas and thoughts at times is very complex, as a written text is the product of a series of complex mental operations. Start is often the hardest part, even if the author has in mind what you mean. However, there are various useful resources to facilitate this process. The purpose of this article is to show some techniques under the phase of the pre-writing for the planning of a written text. These strategies developed through different forms –quick writing, graphics or diagrams– can help the writer to achieve a product textual cohesive and coherent.